New Strategies for Transition-Metal-Catalyzed C–P Bond Formation - Li, Ya-Min; Yang, Shang-Dong (Synlett, 2013)
Summary of recent advancements in the use of Ph2P(O)H and Ph2PTMS as phosphorus sources for the transition-metal-catalyzed C–P bond formation.
Keywords: transition metals; C–P bond formation; Ph2P(O)H